Pembangunan Identitas Komunitas Rohani Authentic Love Family - Amos Hosea Parningotan; Latif Ahmad Fauzan (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study examines the role of the Authentic Love Family (ALF) community in constructing the identities of its members through inclusive philosophies, meaningful social interactions, and innovative communication strategies. Using a qualitative descriptive approach, the research focuses on understanding how ALF creates an environment that fosters spiritual, emotional, and social growth among young Christians. Data were collected through in-depth interviews, participatory observations, and documentation. The findings reveal that ALF’s core philosophy—"To Accept, To Learn, To Freed"—plays a pivotal role in providing members with a safe space for self-expression and self-discovery. Communication channels, including face-to-face interactions and social media platforms, effectively strengthen member relationships and broaden community outreach. The identity construction process involves three key stages: unconditional acceptance, learning new values, and significant behavioral transformation. Members experience increased emotional stability, improved social connections, and a clearer sense of purpose in life. This research contributes to the understanding of how spiritual communities can adapt to modern social dynamics and address the needs of younger generations. The findings also offer practical insights for similar communities seeking to build relevant and inclusive identities in an evolving social landscape.